Synthesis and characterization of rubbery epoxy/organoclay hectorite nanocomposites (eXPRESS Polymer Letters)
The present research investigates the morphology, the mechanical, and the viscoelastic properties of rubbery epoxy/clay nanocomposites synthesized by in situ polymerisation of a prepolymer diglycidyl ether of bisphenol-A crosslinked with an aliphatic diamine based on a polyoxypropylene backbone. The inorganic phase was hectorite, exchanged with octadecylammonium ions in order to give organophilic properties to the phyllosilicate. An ultrasonicator was used to disperse the silicate clay layer into epoxy-amine matrix. The morphology of epoxy-hectorite nanocomposites examined by transmission electron microscopy (TEM) showed that mixed delamination or intercalation or microdispersion could occur depending on type of organoclay. Moreover, the mechanical and viscoelastic properties were found to be improved with only the treated hectorite.